2022
DOI: 10.3389/fpsyg.2021.740444
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Consonant, Rime, and Tone in Mandarin Spoken Word Recognition: An Eye-Tracking Study

Abstract: This study investigated the relative role of sub-syllabic components (initial consonant, rime, and tone) in spoken word recognition of Mandarin Chinese using an eye-tracking experiment with a visual world paradigm. Native Mandarin speakers (all born and grew up in Beijing) were presented with four pictures and an auditory stimulus. They were required to click the picture according to the sound stimulus they heard, and their eye movements were tracked during this process. For a target word (e.g., tang2 “candy”)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…On the other hand, by extending this body of literature, our results showed, for the first time, that in the online processing of coarticulated tones, listeners do not just passively wait for the tonal contexts, but rather actively utilize the heard coarticulated cues and update the activation level of the lexical tones in real time before the tonal contexts are available. Moreover, while various studies have suggested the necessity of including canonical lexical tones in the existing models of spoken word recognition (e.g., Malins and Joanisse, 2010 ; Yang and Chen, 2022 ; Zou et al, 2022 for the TRACE model), the present study further implied that the contextual variation of lexical tones should also be adequately considered.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…On the other hand, by extending this body of literature, our results showed, for the first time, that in the online processing of coarticulated tones, listeners do not just passively wait for the tonal contexts, but rather actively utilize the heard coarticulated cues and update the activation level of the lexical tones in real time before the tonal contexts are available. Moreover, while various studies have suggested the necessity of including canonical lexical tones in the existing models of spoken word recognition (e.g., Malins and Joanisse, 2010 ; Yang and Chen, 2022 ; Zou et al, 2022 for the TRACE model), the present study further implied that the contextual variation of lexical tones should also be adequately considered.…”
Section: Discussionmentioning
confidence: 66%
“…Only the end-state responses were recorded, which have been known to exhibit quite different patterns from the real-time processing in spoken word recognition (e.g., Spivey, 2008 ). While accumulated evidence has shown that just like segments, monosyllabic lexical tones are incrementally processed as the heard speech signals unfold (e.g., Malins and Joanisse, 2010 ; Yang and Chen, 2022 ; Zou et al, 2022 ), it is still unknown how listeners process the coarticulated tones, which are typically surfaced with distorted f0 and thus not the best exemplars of the tones as those over monosyllabic words.…”
Section: Introductionmentioning
confidence: 99%
“…According to information-theoretic methods ( Garner and Miller, 1988 ; Tong et al, 2008 ), in the context of word recognition, the ability of a given signal to constrain recognition is related to its probability of occurring in a corresponding communication system. Due to the small tone inventory compared to that of the segments, each tone occurs more frequently and associates with more words in Mandarin Chinese than consonants and rimes, which makes tone less informative and poorer at constraining word recognition ( Tong et al, 2008 ; Zou et al, 2021 ). Therefore, L2 learners may make less effort on the learning of this unfamiliar suprasegmental contrast which is less informative in constraining word identification compared to segments.…”
Section: Discussionmentioning
confidence: 99%
“…According to informationtheoretic methods (Garner and Miller, 1988;Tong et al, 2008), in the context of word recognition, the ability of a given signal to constrain recognition is related to its probability of occurring in a corresponding communication system. Due to the small tone inventory compared to that of the segments, each tone occurs more frequently and associates with more words in Mandarin Chinese than consonants and rimes, which makes tone less informative and poorer at constraining word recognition (Tong et al, 2008;Zou et al, 2021). Therefore, L2 learners may make less effort on the learning of this unfamiliar suprasegmental contrast which is less informative in constraining word identification compared to segments.…”
Section: Discussionmentioning
confidence: 99%